1981
DOI: 10.1073/pnas.78.5.3190
|View full text |Cite
|
Sign up to set email alerts
|

Presence of autoantibody for phospholipase inhibitory protein, lipomodulin, in patients with rheumatic diseases.

Abstract: The activity of phospholipase inhibitory protein, lipomodulin, partially purified from rabbit neutrophils, was markedly decreased after treatment with sera from patients with rheumatic diseases such as systemic lupus erythematosus, rheumatoid arthritis, and dermatomyositis. The decrease of the protein's inhibitory activity on phospholipase A2 paralleled the amount of [35S]methionine-labeled lipomodulin precipitated by the sera. Absorption ofpatients' sera with anti-human IgM (,u chain) or protein A-agarose, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0
1

Year Published

1982
1982
2005
2005

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(42 citation statements)
references
References 11 publications
1
40
0
1
Order By: Relevance
“…Subsequent work demonstrated the ability of this cell type to respond to GC incubation with over-expression of ANXA 1 (Phillips et al 1989). Consistently, anti-ANXA1 antibodies reversed the inhibitory effect of dexamethasone on arachidonate release (Hirata et al 1981). Activation of human skin fibroblasts provokes intracellular re-location of several annexins, including ANXA1 (Barwise et al 1996), probably with the ultimate effect of controlling cell activation and lipid metabolism (Errasfa et al 1985).…”
Section: Anxa 1 Actions On Other Cellsmentioning
confidence: 62%
See 1 more Smart Citation
“…Subsequent work demonstrated the ability of this cell type to respond to GC incubation with over-expression of ANXA 1 (Phillips et al 1989). Consistently, anti-ANXA1 antibodies reversed the inhibitory effect of dexamethasone on arachidonate release (Hirata et al 1981). Activation of human skin fibroblasts provokes intracellular re-location of several annexins, including ANXA1 (Barwise et al 1996), probably with the ultimate effect of controlling cell activation and lipid metabolism (Errasfa et al 1985).…”
Section: Anxa 1 Actions On Other Cellsmentioning
confidence: 62%
“…Fibroblast/ Synoviocyte -The original work of Hirata et al (1981) described the ability of inhibiting phospholipase A 2 activity in stimulated 3T3 mouse fibroblasts by a purified preparation of ANXA1. Subsequent work demonstrated the ability of this cell type to respond to GC incubation with over-expression of ANXA 1 (Phillips et al 1989).…”
Section: Anxa 1 Actions On Other Cellsmentioning
confidence: 99%
“…Isolation of anti-phospholipase proteins Hirata et al (1980Hirata et al ( , 1981 found that their antiphospholipase protein (lipomodulin) could be purified using a combination of DEAE cellulose and G-75 Sephadex chromatography. We have also found that these techniques are effective for the isolation of the anti-phospholipase protein fractions from the crude peritoneal proteins.…”
Section: Phospholipase A2 Assaymentioning
confidence: 99%
“…By inhibiting phospholipase A2, certain steroids prevent the biosynthesis by cells of pro-inflammatory mediators such as the prostaglandins, hydroxy-acids and leukotrienes (Gryglewski, Panczenko, Korbut, Grodzinska & Ocetkiewicz, 1975;Hong & Levine, 1976; Nijkamp, Flower, Moncada & Vane, 1976;Tam, Hong & Levine, 1977;Blackwell, Flower, Nijkamp & Vane, 1978;Flower & Blackwell, 1979;Di Rosa & Persico, 1979;Hirata, Schiffman, Venkatasubramanian, Salomon & Axelrod, 1980;Blackwell, Carnuccio, Di Rosa, Flower, Parente & Persico, 1980; Hirata, Del Carmine, Nelson, Axelrod, Schiffman, Warabi, De Blas, Nirenberg, Manganiello, Vaughan, Kumagai, Green, Decker & Steinberg, 1981;Carnuccio, Di Rosa, Flower & Pinto, 1981). This effect is specific for the glucocorticoids (Hong & Levine, 1976;Nijkamp etal., 1976;Tam etal., 1977;Blackwell et al, 1978;Flower & Blackwell, 1979;Di Rosa & Persico, 1979;Carnuccio et al, 1980;Hirata etal., 1980;Blackwell et al, 1980;Hirata etal., 1981), and depends upon receptor occupation as well as transcriptional and translational events within the target cells (Danon & Assouline, 1978;Russo-Marie, Paing & Duval, 1979;Flower & Blackwell, 1979;Di Rosa & Persico, 1979;Carnuccio et al, 1980;Hirata etal., 0007-1188/82/050185-10 $01.00 1980; Blackwell etal., 1980;Hirataetal., 1981).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation